Biocontrol Microneedle Patch: A Promising Agent for Protecting Citrus Fruits from Postharvest Infection - Ling Jiang; Huan Huang; Xingyu Shi; Jian Wu; Juexian Ye; Qian Xu; Shaobin Fang; Chuanbin Wu; Rui Luo; Chao Lu; Daojun Liu (MDPI AG, 2023)
With increasing human awareness of food safety, the replacement of highly toxic pesticides with biocompatible antimicrobials has become a trend. This study proposes a biocontrol microneedle (BMN) to expand the application of the food-grade preservative epsilon-poly-L-lysine (ε-PL) in fruit preservatives by utilizing a dissolving microneedle system. The macromolecular polymer ε-PL not only possesses broad-spectrum antimicrobial activity but also exhibits good mechanical properties. With the addition of a small amount of polyvinyl alcohol, the mechanical strength of the ε-PL-based microneedle patch could be further improved to achieve an enhanced failure force of needles at 1.6 N/needle and induce an approximately 96% insertion rate in citrus fruit pericarps. An ex vivo insertion test revealed that the microneedle tips could be effectively inserted into the citrus fruit pericarp, rapidly dissolve within 3 min, and produce inconspicuous needle holes. Moreover, the high drug loading capacity of BMN was observed to reach approximately 1890 μg/patch, which is essential for enhancing the concentration-dependent antifungal activity of ε-PL. The drug distribution study has confirmed the feasibility of mediating the local diffusion of EPL in the pericarp through BMN. Therefore, BMN has great potential to reduce the incidence of invasive fungal infections in local areas of citrus fruit pericarp.